2014
DOI: 10.1016/j.cej.2014.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Air–steam gasification of sewage sludge in a fluidized bed. Influence of some operating conditions

Abstract: An experimental work was carried out to investigate the viability of energy recovery from the air-steam gasification of sewage sludge. The relative influence of different factors, as well as the effect of their possible interactions, has been determined by means of analysis of variance. Temperature was found to be the most influential factor for most of the variables analyzed. Solid yield (35-41 wt. %) and tar content (11-45 g/m 3 STP ) were largely reduced with temperature, whereas gas production (0.89-1.32 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 30 publications
2
38
1
1
Order By: Relevance
“…%, thus improving the carbon conversion obtained in the direct gasification of sewage sludge. [23], it can be observed that the production of gas has been reduced by half, mainly due to the higher ash content in char. The production of gas during the pyrolysis stage (around 0.06-0.07 m 3 STP N 2 -free/kg SS) is not high enough to offset the difference in the production of gas from the gasification of both materials.…”
Section: Solid Yield and Carbon Fraction Remaining As Solidmentioning
confidence: 85%
See 4 more Smart Citations
“…%, thus improving the carbon conversion obtained in the direct gasification of sewage sludge. [23], it can be observed that the production of gas has been reduced by half, mainly due to the higher ash content in char. The production of gas during the pyrolysis stage (around 0.06-0.07 m 3 STP N 2 -free/kg SS) is not high enough to offset the difference in the production of gas from the gasification of both materials.…”
Section: Solid Yield and Carbon Fraction Remaining As Solidmentioning
confidence: 85%
“…Furthermore, as a result of the ANOVA analyses, Table 5 presents a summary of the ANOVA results obtained when sewage sludge was the feedstock for the gasification process [23]. This comparative study is based on a single type of sewage sludge and char.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations